Model Senam Pekerja untuk Meningkatkan Produktivitas Kerja Buruh - Setiawan, Arif (Media Ilmu Keolahragaan Indonesia, 2014)
Work performed labor is a type of work that requires only a simple motor skills but should be done continuously for several hours without pause. This condition in the long run potentially detrimental to health. To that end, after a through study kinesiology analysis of the dominant motions performed daily laborers in the work, creates a model of exercises that are intended to be to relax the muscles, stretch the joints, maintains extensive ranges of motion (range of motion), improve blood circulation edge, reduce saturation due to motion routines. Exercise is also designed to provide benefits for work to restore the sensitivity of sensory-motor nerves, reduce fatigue, reduce the possibility of faulty work, restore (recovery) initial fitness level as before the start of work and prevent the occurrence of abnormal posture due to the working position is maintained for a long time.Â